The Effect of a Suggested Training Program (Physical –psychological) on Some Physiological Variables and External Control Spot Of Table-tennis Players - Salem, Agharid (Journal of Physical Education, 2017)
This study aims at identifying the effect of the proposed training program (physical –psychological) on some physiological varieties (Cholesterol, Triglyceride, H.D.L, V.L.D.L,L.D.L) and external control spot. The subjects of the research included 5 elite players of Iraqi (from Baghdad) national table-tennis team. The application of the program lasted for 10 weeks, 3 training units per week, (120) minutes for each training unit. The results of the research have concluded that the suggested training program has achieved a development in physiological varieties understudy and an improvement in controlling spot (from external controlling spot to internal controlling spot). Due to the positive effects on physiological and psychological varieties of the study, the two researchers have recommended includinge this suggested training program in the training of table-tennis game, to conduct similar studies on other individual and collective games and to prepare psychological training programs suitable for each game which will upgrade the level of sports.